Detection of c-erbB-2 mRNAs Using Dig-Labelled Oligonucleotide Probe with in situ Hybridisation in Human Breast Carcinoma: Comparison with Immunohistochemical Results - Melek Öztürk; Sema Bolkent; Selma Yilmazer; Gültekin Kaner; Hilal Ünal (Analytical Cellular Pathology)
Amplification and overexpression of the c-erbB-2 oncogene are of prognostic significance in human breast cancer. Overexpression of c-erbB-2 is the result of gene amplification. However, increased transcript levels of c-erbB-2 are also detected in the absence of gene amplification. In this study for the detection of the overexpression mRNA in situ hybridisation (ISH) and immunohistochemistry (IHC) were used. Our aim was to develop the suitable mRNA ISH protocol for formalin-fixed paraffin-embedded material and to compare the localisation of transcripts and protein products in 20 primary breast carcinomas. Sections were immunostained with monoclonal c-erbB-2 antibody. In ISH method digoxigenin-labelled oligoprobe was used for the detection of c-erbB-2 mRNAs. We determined optimal condition for the ISH procedure (e.g., probe concentration, digestion, post washing). c-erbB-2 protein overproduction was detected in 11/20 cases with IHC. The mRNA signals were observed in malignant cell cytoplasm in 6/20 cases by ISH. ISH positive signals were found in only one case without detected overexpression of the protein. There were cell to cell variations in the hybridisation signals even within individual tumours. The ISH and IHC positive signals for c-erbB-2 was observed mostly in infiltrating ductal carcinomas that belong to aggressive lesions.